Implementation of Endoscopic Submucosal Dissection for Early Colorectal Neoplasms in Sweden - Henrik Thorlacius; Noryia Uedo; Ervin Toth (Gastroenterology Research and Practice)
Objectives. Endoscopic submucosal dissection (ESD) is an effective method for en bloc removal of large colorectal tumors in Japan, but this technique is not yet widely established in western countries. The purpose here was to report the experience of implementing colorectal ESD in Sweden. Methods. Twenty-nine patients with primarily nonmalignant and early colorectal neoplasms considered to be too difficult to remove en bloc with EMR underwent ESD. Five cases of invasive cancer underwent ESD due to high comorbidity excluding surgical intervention or as an unexpected finding. Results. The median age of the patients was 74 years. The median tumor size was 26 mm (range 11–89 mm). The median procedure time was 142 min (range 57–291 min). En bloc resection rate was 72% and the R0 resection rate was 69%. Two perforations occurred amounting to a perforation rate of 6.9%. Both patients with perforation could be managed conservatively. One bleeding occurred during ESD but no postoperative bleeding was observed. Conclusion. Our data confirms that ESD is an effective method for en bloc resection of large colorectal adenomas and early cancers. This study demonstrates that implementation of colorectal ESD is feasible in Sweden after proper training, careful patient selection, and standardization of the ESD procedure.